Handling TikTok App Addiction Behavior in Gen Z (Case Study on Three Teenagers in Rumah Tiga Village) - Rachel Krestina Huwae; Fatimah Azis (Syntax Idea)
Indonesia is the second country with the most active TikTok users in the world. In April 2022, active TikTok users in Indonesia reached 99.1 million people. revealed in the latest report 'Media State of Mobile 2024' released by Data.AI at the beginning of 2024, Indonesians are also starting to get addicted to TikTok. It was recorded that Indonesian citizens spent 64.8 billion hours on TikTok throughout 2023, an increase of 33%. This proves that many people are addicted to TikTok. Especially Gen Z, which is a generation that is close to technology (digital native), as they were born in the era of cellphones, are smart, grew up with sophisticated computer technology, and have an openness to easier internet access compared to previous generations. So efforts are needed to overcome Gen z who is addicted to the Tiktok application (Tiktok Syndrome). The aim of this research is to answer the problem of how to handle children addicted to the Tiktok application (Tiktok syndrome) in 3 teenagers in Rumah Tiga Village, Teluk Ambon District, Ambon City.